Islamic Law, Slavery, and Feelings: A Fourth/Tenth-Century Andalusi Notarial Model on the Manumission of an Unruly and Bad-Tempered Female Slave - Puente González, Cristina de la (Hawwa, 2021)
Abstract This article studies a fourth/tenth-century notarial model to limit and place conditions on (istirʿāʾ) the manumission of an unruly and bad-tempered female slave. The text is part of al-Wathāʾiq wa-l-sijillāt, a notarial manual compiled by Cordoban scholar Ibn al-ʿAṭṭār (d. 399/1009), the earliest edited Andalusi work of this genre. Although it is part of a chapter on slavery and, more specifically, of a section dedicated to the manumission of slaves, it is not a generic notarial text dealing with the manumission of female slaves. The document is not a manumission form, but one that complements and limits a manumission; in fact, its aim is to impede or overturn the process. The article studies this notarial model in three different contexts: (1) Andalusi kutub al-wathāʾiq, (2) Mālikī legal literature on slavery and (3) notarial model reservation testimonies. Even if, at first glance, it appears to be an unusual legal document, when analysing other Mālikī sources we observe that the text is part of a well-documented tradition with widely accepted legal justification. This model is nevertheless exceptional from a procedural point of view because its legal arguments are based on feelings and refer specifically to the slave’s personality, temperament and behaviour as the factors that motivated the legal act.